THE INFLUENCE OF BOARD MEETINGS, ENVIRONMENTAL PERFORMANCE, AND FIRM SIZE ON PROFITABILITY - Cynthia Tjahjadi; Rousilita Suhendah (International Journal of Application on Economics and Business, 2026)
The purpose of this research is to obtain empirical evidence regarding the influence of board meetings, environmental performance, and firm size on profitability in manufacturing companie within the basic materials and non-cyclical consumer sub-sectors listed on the Indonesia Stock Exchange (IDX) during the 2021-2023 period. Using a sample of 49 companies out of a total of 243 companies selected through a purposive sampling method, this study applies multiple linear regression analysis and processes the data using Excel and Eviews 12 software. The findings indicate that board meetings have no effect on profitability. In addition, environmental performance has a positive effect on profitability, whereas firm size has a negative effect on profitability.